Silas McMullen interviewed by John Meredith for the John Meredith folklore collection - McMullen, Silas, 1894-; Meredith, John, 1920-2001. (1986)
Folkloric recording. Silas McMullen talks about life around Wattagan Creek. McMullen speaks about family background; rust in wheat; self-sufficiency of farmers; horse transport; wheat threshing with horse power; corn harvesting; school at Dairy Arm; yeast for bread making; curing meat; ploughing; before income tax and rates; cattle grazing; planting; lighthouse on Mount Warrawolong; superstitions; weeds and pests; two rail and dogleg fences; timber uses; changes in cattle population; blackberries; sawpits.
Reels 179 to 196 were recorded from 25 to 30 May 1986 as part of a project to record the oral history of Wollombi Valley farming community.
Recorded at Wattagan Creek, New South Wales on 29 May 1986.
Also available online
Keywords: McMullen, Silas, -- 1894- -- Interviews; Farm life -- New South Wales -- Wollombi Region; Wollombi Region (N.S.W.) -- History; Wollombi Region (N.S.W.) -- Rural conditions